Apollo's arrow ebook The profound and enduring impact of coronavirus on the way we live. - Christakis, Nicholas A. (2020)
A piercing and scientifically grounded look at the emergence of the coronavirus pandemic and how it will change the way we live—"excellent and timely." ( The New Yorker )   Apollo's Arrow offers a riveting account of the impact of the coronavirus pandemic as it swept through American society in 2020, and of how the recovery will unfold in the coming years. Drawing on momentous (yet dimly remembered) historical epidemics, contemporary analyses, and cutting-edge research from a range of scientific disciplines, bestselling author, physician, sociologist, and public health expert Nicholas A. Christakis explores what it means to live in a time of plague—an experience that is paradoxically uncommon to the vast majority of humans who are alive, yet deeply fundamental to our species. Unleashing new divisions in our society as well as opportunities for cooperation, this 21st-century pandemic has upended our lives in ways that will test, but not vanquish, our already frayed collective culture. Featuring new, provocative arguments and vivid examples ranging across medicine, history, sociology, epidemiology, data science, and genetics, Apollo's Arrow envisions what happens when the great force of a deadly germ meets the enduring reality of our evolved social nature.